PEMBINAAN ANAK JALANAN MELALUI HOME SHELTER âGRIYA BACAâ KOTA MALANG SEBAGAI UPAYA MENUJU KOTA LAYAK ANAK - SETIAWAN, ERFINANDUS G.; WAHYUDI, CATUR; JATMIKOWATI, SRI HARTINI (PUBLISIA (Jurnal Ilmu Administrasi Publik), 2016)
Home Shelter "Griya Baca" of the places for training street children and a non-profit organization. The function and purpose of home shelter âGriya Bacaâ is to accompany and steer of street children to find the identity, and facilitate the process to achieve his goals. Another function that becomes the institutional mission is to reduce the rate of growth of street children in Malang City. The activities of home shelter âGriya Bacaâ is coaching about spiritual values ââand morality asbasis capital for changing of behavior patterns without any sense of presure.